1989
DOI: 10.1210/endo-125-5-2392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolactin Versus Growth Hormone on Islet Function and the Importance of Using Homologous Mammosomatotropic Hormones*

Abstract: The purpose of this study was to determine the effects of homologous rat PRL (rPRL) and rat GH (rGH) on islet B-cell function in neonatal and adult rat islets in vitro. In neonatal rat islets, exposure to rPRL for more than 24 h was necessary for a stimulatory effect on insulin secretion. By day 4, insulin secretion was 3.8-fold greater in the islets cultured with rPRL. rGH had a modest effect on insulin secretion, and this effect was additive with that of rPRL. Both rPRL and rGH increased islet insulin conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 19 publications
3
27
0
2
Order By: Relevance
“…Therefore, most B-cells in the last third of pregnancy may no longer proliferate in response to lactogenic hormones. Several in vivo and in vitro studies have shown that prolonged stimulation of islets by lactogenic hormones can maintain the enhanced islet functions for extended periods (3,4,21). These results suggest the possibility that a downregulation mechanism may exist on the function of islet B-cells in the last third of pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, most B-cells in the last third of pregnancy may no longer proliferate in response to lactogenic hormones. Several in vivo and in vitro studies have shown that prolonged stimulation of islets by lactogenic hormones can maintain the enhanced islet functions for extended periods (3,4,21). These results suggest the possibility that a downregulation mechanism may exist on the function of islet B-cells in the last third of pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Table 2 summarizes the reported actions of GH-related hormones in various types of insulin-secreting cells. In addition to their mitogenic effect [4][5][6][7][8][9][10][11], these hormones are known to stimulate insulin biosynthesis [6,9,[12][13][14], to promote oxidative metabolism of glucose [7,9], and to increase GLUT2 expression [15], thereby contributing to the functional maturation (increase in sensitivity to glucose for the stimulation of insulin secretion) of /3-cells [14][15][16]. In view of these various effects of GH-related peptides in /3-cells, to study their mode of action might reveal crucial mechanisms for the regulation of growth and the function of these cells, which are only partially understood [2,17].…”
Section: Gh and Prl As Growth/differentiationmentioning
confidence: 99%
“…Among these hormones, prolactin (PRL) plays an important role in the maturation of the glucose sensing mechanisms. In fact, PRL treatment affects several physiological parameters of pancreatic B-cell, such as the glucose-induced reduction of K+ permeability [4], the glucose stimulation threshold [5], cell-to-cell coupling [5], [3H]thymidine incorporation [6] and the proliferation of j&cells in vitro [7]. GLUT2, the liver/j?cell glucose transporter, plays a key role in the glucose sensing apparatus [8].…”
Section: Introductionmentioning
confidence: 99%